2009
DOI: 10.1143/jjap.48.06fh01
|View full text |Cite
|
Sign up to set email alerts
|

Fine Pattern Fabrication by the Molded Mask Method (Nanoimprint Lithography) in the 1970s

Abstract: Nanoimprint lithography has recently been attracting the attention of many researchers in the field of nanofabrication technology. Although the study of nanoimprint lithography was initiated by Chou et al. around 1995, a fine-pattern fabrication technology, whose concept is similar to nanoimprint lithography, had been proposed and studied at NTT Laboratories in Japan as early as in the 1970s. The technology was based on the combination of the molding of plastic film on a substrate and dry etching of the molded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…We conducted feasibility studies in the 1970s on the molded mask method and demonstrated its technical features and applicability as a novel technology for fabricating devices and components [4,[11][12][13][14][15][16]. One decade after the invention of the molded mask method, Napoli and Russell filed their patent in the United States and another decade later the studies by S. Y. Chou and C. G. Willson were reported.…”
Section: Background Of the Molded Mask Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted feasibility studies in the 1970s on the molded mask method and demonstrated its technical features and applicability as a novel technology for fabricating devices and components [4,[11][12][13][14][15][16]. One decade after the invention of the molded mask method, Napoli and Russell filed their patent in the United States and another decade later the studies by S. Y. Chou and C. G. Willson were reported.…”
Section: Background Of the Molded Mask Methodsmentioning
confidence: 99%
“…Therefore, we can trace the origin of nanoimprint lithography back to the molded mask method invented in the 1970s. Figure 1 shows the basic concept behind the molded mask method and shows that it is essentially the same as present-day nanoimprint lithography [4,[11][12][13][14][15][16].…”
Section: Background Of the Molded Mask Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanoimprint lithography (NIL) was invented and demonstrated in the 1970s by Susumu Fujimori at NTT in Japan, but it was not until 1995 when Stephen Chou and coworkers at the University of Minnesota (later at Princeton University) published their first results that NIL started to gain broader attention, by demonstrating 10-nm-imprint capabilities at a time when 50 nm was considered as the resolution limit of projection lithography (see Figure 2) [7,8]. At that time, X-ray proximity lithography (using 1.3-nm wavelength) was seen as an alternative to DUV projection, using 248-nm light from KrF-excimer lasers.…”
mentioning
confidence: 99%